Formation of Ethical Competences for AI Use in English Foreign Language Teachings - Clara Abisheva; Zina Koldasbaeva; Nazym Nossiyeva; Nazilya Irgebaeva; Аinash Aipova; Saule Doldinova; Samat Smoilov; Ryskeldy Aykenova; Lyazzat Umirzakova; Mapruza Idrissova (Qubahan Academic Journal)
As artificial intelligence (AI) has become increasingly significant in education, the lack of teacher readiness continues to hinder its effective use in language teaching in Kazakhstan. This study aims to address this gap by exploring EFL teachers’ experiences with AI integration and assessing their ethical competences. Using a mixed-methods approach, quantitative and qualitative data from survey and semi-structured interviews (further coded, and thematically analyzed) were collected from 60 English language teachers from different universities in Kazakhstan. The results indicated that language teachers were least confident in ethical use of AI in language teachings. The findings revealed the finalized six main ethical competences and 24 sub-competences, including (i) AI literacy competence, (ii) pedagogical and technical competence, (iii) assessment and reflection competence, (iv) facilitation of student autonomy competence, (v) professional and legal ethics competence, and (vi) responsibility and accountability competence. These competences offer a framework for developing future EFL teaching and learning programs that maximize AI’s benefits while addressing potential ethical challenges.